TECHNOLOGY-BASED DIFFERENTIATED LEARNING WITH THE ETHNOMATHEMATICAL CONTEXT OF BIMA WOVEN FABRIC TO ENHANCE STUDENTS’ MATHEMATICAL LITERACY AND CHARACTER EDUCATION - Anisa, Nur; Ramdani, Nurlailatun; Juliawan, Rizcky (Prima: Jurnal Pendidikan Matematika, 2025)
Mathematical literacy skills play a crucial role in enabling students to take on constructive, active, and reflective roles in facing global challenges in the 21st century. However, observations at SMPN 4 Woha revealed that students' mathematical literacy remains low due to the use of conventional teaching methods. This study aims to describe the implementation process of technology-based differentiated learning within the context of ethnomathematics using Bima woven fabric motifs, in an effort to enhance students’ mathematical literacy and character education. A qualitative approach was employed, using purposive sampling to select three students from a total of 20 seventh-grade students as research subjects. The instruments used included tests, interviews, and questionnaires. Data were analyzed descriptively. The findings indicate that the implementation of technology-based differentiated learning with the context of Bima woven fabric ethnomathematics has a significant impact on improving students’ mathematical literacy and strengthening their character education.